Comparative Analysis Of Decision Support Systems Determining The Right Food Business Location In Binjai City Using Topsis And Saw Methods - Retno Hidayati; Novriyenni Novriyenni; Nurhayati Nurhayati (CV. AFDIFAL MAJU BERKAH, 2024)
Every year, the development of the business world continues to increase. The location to open a business in accordance with the sales target in accordance with the market share is very difficult. In order to provide the right decision in choosing a business location, a method is needed in making decisions. Materials (data) and Methods: The business locations processed in this study were 6 types of criteria, namely the number of competitors, the level of population density, the number of supporting businesses around the location, business location permits, business position and traffic access. The method used in processing the data is SAW and Topsis. The stages of processing the SAW and Topsis methods in this research are initializing the wood data. The result of dividing and then multiplying all the criteria according to the weights. Then in the end, the highest preference value will be obtained for each alternative. The result of testing this method is ranking. The best ranking is the ninth alternative. This result has 90% accuracy. The choice of business location can be done optimally. So that the results of the decisions that have been obtained can be used as a guide for choosing a business location that is in accordance with the target market to be achieved.